PENGARUH LOKASI, PELAYANAN DAN CITRA TERHADAP GAYA HIDUP DAN MINAT BELI MASYARAKAT DI MAKASSAR MALL - Ruslan, Reka; Mappatompo, Andi; Syafaruddin, Syafaruddin (COMPETITIVENESS, 2021)
This study aims to examine the effect of location, service, image, and lifestyle as moderating variables on people's buying interest in Makassar Mall. The type of research used in this research is experimental research. The research design used is a quantitative approach. This research was conducted in Makassar Mall. The number of samples in this study was 185 people who shopped at Makassar Mall. The sampling technique is accidental sampling. The instrument used in this study was a questionnaire or google form with data collection techniques, namely the provision of questionnaires. The collected data was then analyzed using descriptive statistics, inferential statistics, and path analysis. The results showed that the variables of location, service, image had a significant positive effect on lifestyle. Furthermore, the location and service variables have a significant positive effect on consumer buying interest, while the image has no significant positive effect on consumer buying interest. Furthermore, lifestyle variables have a significant effect on buying interest at Makassar Mall. The location has a significant effect on consumer buying interest through lifestyle. Meanwhile, service has a significant positive effect on consumer buying interest through lifestyle and image has a significant effect on consumer buying interest through lifestyle. Based on the results of the study, it is illustrated that the results of path analysis on 3 variables X and Y1 then the X variable (location, service, and image) affect Y (lifestyle). While the influence of X (location and service) has a significant positive effect on Y2 (consumer buying interest), while the X3 variable (image) does not affect consumer buying interest. Furthermore, for the influence of the Lifestyle variable, it was obtained that it had a significant effect on buying interest. The results of the path analysis showed that the location, service, and image variables had a significant effect on consumers' buying interest through lifestyle.Keywords: Location, Service, Image, Lifestyle, Buying Interest